VENTILATOR ASSOCIATED PNEUMONIA: A SYSTEMATIC APPRAISAL IN A SAUDI ARABIAN CONTEXT - Jong, Catherine; Mortell, Manfred (THE MALAYSIAN JOURNAL OF NURSING (MJN), 2020)
Background:Ventilator-associated pneumonia (VAP) is the commonest hospital-acquired infection (HAI) in intensive care. The incidence of VAPis the leading cause of HAI in the ICU. In the United States of America, VAPis the second most prevalent HAI with a reported mortality of 40-80%. However, despite transparency in the literature on the preventative measures in the preceding decade, the prevalence of VAPremains high in mechanically ventilated patients and increases an ICU patient's confinement by 5-7 days once they developed a VAP.Methods:To determine the incidence, prevalence, and aetiology of VAPand oral care practices in Saudi Arabia, a systemic review of the literature published from the year 2000 till present day was employed. Databases searched included CINAHL, WILEY, PROQUESTand SCIENCE DIRECT. The systematic collection of data was followed by the development of the appraisal protocol which set out the methods in the appraisal This protocol specifies the appraisal question, inclusion and exclusion criteria, databases search strategies, study selection, quality appraisal and data production as well as the individual types of studies sited, appraised and synthesized.Results:The findings from the systematic appraisal indicate that implementing a comprehensive and effective oral care protocol which incorporates both the application of an antiseptic such as Chlorhexidine 0.12% and the clinical practice of tooth-brushing plays an instrumental role in preventing and reducing VAPin the intubated, mechanically ventilated ICU patient.Conclusions:VAPremains a common cause of HAI, but in order to stay current and compliant with knowledge and practical skills, ICU nurses require ongoing evidence-based education, reinforced with evidence-based practice. In addition to encouraging development of a body of knowledge that will advance nursing practice which is clinically safe and effective.